The forgotten founders : rethinking the history of the Old West - Udall, Stewart L. (Island Press ; Shearwater Books, 2002)
A critical examination of traditional American West history asserting that families rather than gunslingers were the key players; discusses explorers, fur trappers, clergy, the Gold Rush, and the building of communities.